1978
DOI: 10.1136/bmj.2.6153.1682
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin in epilepsy and hysteria.

Abstract: Differentiating between hysteria presenting in an epileptiform manner and epilepsy can present diagnostic difficulties. Differentiation is important, however, since management of the two disorders differs. Electrochemical stimulation of the medial basal hypothalamus in animal models increases prolactin release.' Therefore if the abnormal electrical activity in epilepsy passes through the midbrain it should raise the serum prolactin concentration. This paper reports an investigation of this hypothesis.Patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
3

Year Published

1982
1982
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(95 citation statements)
references
References 0 publications
2
90
0
3
Order By: Relevance
“…The PRL also rose 20 minutes -83 -after complex partial seizures, but not with simple partial attacks, the latter, by definition, having no alterations of consciousness. These results confirm the findings of others (Trimble 1978a;Abbott et al 1980;Collins et al 1982;Hoppener et al 1982), who found PRL elevation 15 to 20 minutes after major generalised tonic-clonic seizures and ECT, but not with hysterical attacks. Hoppener et al (1982) also reported elevated PRL levels in 8CY/o of patients with complex partial seizures.…”
Section: Gamma-aminobutyric Acid (Gaba)supporting
confidence: 82%
“…The PRL also rose 20 minutes -83 -after complex partial seizures, but not with simple partial attacks, the latter, by definition, having no alterations of consciousness. These results confirm the findings of others (Trimble 1978a;Abbott et al 1980;Collins et al 1982;Hoppener et al 1982), who found PRL elevation 15 to 20 minutes after major generalised tonic-clonic seizures and ECT, but not with hysterical attacks. Hoppener et al (1982) also reported elevated PRL levels in 8CY/o of patients with complex partial seizures.…”
Section: Gamma-aminobutyric Acid (Gaba)supporting
confidence: 82%
“…Elevated serum PRL among patients with generalized epileptic seizures (ES) helped distinguish epilepsy from PNES. 88 Many studies have since been conducted measuring PRL among patients with PNES, finding that when PRL did not rise postictally, the average sensitivity to PNES was 89% across the studies. 89 Furthermore, studies of PRL in ES versus PNES have since shown that serum levels are elevated on average in 88% of generalized tonic clonic (GTC) epileptic seizures, in 64% of temporal lobe complex partial epileptic seizures (CPSs), and in 12% of simple partial epileptic seizures.…”
Section: Pnesmentioning
confidence: 99%
“…A five to thirty-fold rise of prolactin above baseline levels can be measured approximately 20 minutes after the majority of tonic clonic generalized seizures, after most complex partial seizures but only after some simple partial attacks. Such a rise is never present after convulsive pseudoseizures (Trimble, 1978(Trimble, , 1986. A gradual lessening of the expected prolactin rise occurs when serial epileptic seizures occur one after another: exhaustion of the central pituitary prolactin store may be the cause (Berkovic, 1984).…”
Section: Neurohuldoral Studiesmentioning
confidence: 99%